1999
DOI: 10.1159/000019090
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequences Specific for Nonnominal Immunoglobulin Allotypes in Rheumatoid Arthritis Patients and in Normal Individuals and Their Expression in Synovial Tissue of Rheumatoid Arthritis Patients

Abstract: The production of antibodies against nonnominal immunoglobulin allotypes in rheumatoid arthritis (RA) patients suggests that the immune system of these patients has been exposed to such foreign allotypes. The presence of nonnominal allotypes is, however, a genetic enigma. We searched for nucleotide sequences specific for nonnominal G3mg and G3mb copies in individuals homozygous for these alleles. Using a sensitive and specific nested polymerase chain reaction (PCR) method with genomic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, our observations of the hidden allotype genes [30] show that the DNA sequences for the hidden allotypes are present in normal genomic configurations and that the fragment is normally spliced in the expressed form. It is thus not likely that the hidden allotype genes are transported by a retrovirus.…”
Section: Viral High-jacking and Transfer Of Human Genesmentioning
confidence: 68%
See 2 more Smart Citations
“…However, our observations of the hidden allotype genes [30] show that the DNA sequences for the hidden allotypes are present in normal genomic configurations and that the fragment is normally spliced in the expressed form. It is thus not likely that the hidden allotype genes are transported by a retrovirus.…”
Section: Viral High-jacking and Transfer Of Human Genesmentioning
confidence: 68%
“…Starting with model experiments, we have focused on the G3m(b) and (g) allotypes because their restriction endonuclease cleavage sites are well known [24]. Recently, by nested PCR, we have for the first time defined hidden allotypes at the genomic level [30]. We also observed that the number of copies of these genes is so small that a Mendelian inheritance is excluded.…”
Section: Hidden or Non-nominal Allotypes Violating Mendelian Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, detecting antibodies with a foreign allotype indicates the immunological activity of microchimeric cells. For instance, patients with rheumatoid arthritis were found to produce antibodies targeting foreign immunoglobulin allotypes [57,58]. Moreover, the corresponding genes of these extrinsic immunoglobulins were detected in synovial tissues by polymerase chain reaction, suggesting a microchimerism involvement [57].…”
Section: Discussionmentioning
confidence: 99%